On the Transformations Preserving Asymptotic Directions of Hypersurfaces in the Euclidean Space - Alagoz, Yasemin; Soyucok, Ziya (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2009)
We consider the transformations preserving asymptotic directions of hypersurfaces in n-dimensional Euclidean space and we obtain a system of equations which must be satisfied by transformations.
Keywords: Hypersurfaces; asymptotic directions; Mathematics